Asuransi Kebencanaan dalam Perekonomian Nasional dan Daerah - Tatok Djoko Sudiarto (Universitas Paramadina, 2016)
AbstrakThe series of disasters that occurred late show is still much work to be completed by the various parties, namely the Government, Private / World of Business and Society. Included in this is the local society in terms of the decentralization policy, to reduce the risk and impact of disasters. One of the strategic effort should continue to be pursued in order to achieve disaster risk reduction program is to encourage people to